2021
DOI: 10.3390/jof7040283
|View full text |Cite
|
Sign up to set email alerts
|

Weeds as Pathogen Hosts and Disease Risk for Crops in the Wake of a Reduced Use of Herbicides: Evidence from Yam (Dioscorea alata) Fields and Colletotrichum Pathogens in the Tropics

Abstract: The transition toward sustainable agriculture requires rethinking cropping systems in the light of less intensive and chemically reliant practices. Weed management is one of the target practices to evolve cropping systems with decreased impact on the environment. While softened management will lead to increased weeds/crops coexistence, it is of importance to assess the relative benefits and drawbacks of new practices. Among the potential drawbacks of weeds/crops coexistence, disease risk may increase if weeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Leaf age was differentiated as follows: old leaves are darker green, often demonstrating traces of damage (herbivory or dry necrosis spots) and are located deeper on ramets, while young leaves are light green and fresh/recent and without signs of damage, and they are located at proximal tips of ramets. Back in the lab, leaves were rinsed in short baths of diluted bleach solution, methanol, and decontaminated water, respectively [34]. Then, three leaf areas were cut, near the stem, mid-leaf, and near the drip tip.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaf age was differentiated as follows: old leaves are darker green, often demonstrating traces of damage (herbivory or dry necrosis spots) and are located deeper on ramets, while young leaves are light green and fresh/recent and without signs of damage, and they are located at proximal tips of ramets. Back in the lab, leaves were rinsed in short baths of diluted bleach solution, methanol, and decontaminated water, respectively [34]. Then, three leaf areas were cut, near the stem, mid-leaf, and near the drip tip.…”
Section: Methodsmentioning
confidence: 99%
“…Then, three leaf areas were cut, near the stem, mid-leaf, and near the drip tip. For each of these leaf areas, two pieces were cut for replication, and one piece was placed on a Petri dish with simple agar media and the replication was placed on a Petri dish with S medium [34] to favor growth of Colletotrichum over other fungi; these steps were processed in sterile conditions under a laminar flow cabinet (model LRF 48). Both replicates were nevertheless recorded as either positive (one or two Colletotrichum strains identified) or negative (no Colletotrichum growth in either piece).…”
Section: Methodsmentioning
confidence: 99%
“…Besides, weeds could act as pathogen reservoirs, increasing the disease risk to yam plants. It is, therefore, important to develop environment friendly and economically sustainable strategies for weed management in yam plantations ( Dentika et al, 2021 ). The development of gene-edited herbicide-tolerant yam accessions can effectively alleviate the weed challenge while alleviating crop phytotoxicity due to the reduced need for repeated use of chemical herbicides.…”
Section: Potential Applications For Improvement Of Staple Crops In Af...mentioning
confidence: 99%
“…Indeed, weeds have proven to be an important reservoir for Colletotrichum pathogens, and they contribute to the initiation of local disease (Dentika et al, 2021). Recent findings have emphasized subspecialization of Colletotrichum congenerics on weed communities at the local level, and the potential antagonism between species of the C. gloeosporioides complex and the C. truncatum complex (Dentika et al, 2021). We therefore investigated whether C. truncatum inoculation in yams would confer a protective effect against C. gloeosporioides species and anthracnose disease development.…”
mentioning
confidence: 99%
“…Studies have shown that local dispersal often plays a significant role in local disease events (Dentika et al, 2022;Penet et al, 2014), in addition to an important genetic variability even at field level (Frézal et al, 2018), possibly due to inocula from local vegetation. Indeed, weeds have proven to be an important reservoir for Colletotrichum pathogens, and they contribute to the initiation of local disease (Dentika et al, 2021). Recent findings have emphasized subspecialization of Colletotrichum congenerics on weed communities at the local level, and the potential antagonism between species of the C. gloeosporioides complex and the C. truncatum complex (Dentika et al, 2021).…”
mentioning
confidence: 99%